A Comparison of Pavlik Harness Treatment Regimens for Dislocated But Reducible (Ortolani+) Hips in Infantile Developmental Dysplasia of the Hip. Issue 10 (November 2019) - Hines, Adam C.; Neal, David C.; Beckwith, Terri; Jo, ChanHee; Kim, Harry K.W.
Abstract : Background: Variation exists in the Pavlik harness (PH) treatment regimen for infantile developmental dysplasia of the hip (DDH). The purpose of this study was to determine if the daily PH wear duration (23 vs. 24 h) and frequency of follow-up visits affect the clinical and radiographic outcomes of infants with dislocated but reducible (Ortolani+) hips. Methods: This study reviewed prospectively enrolled patients with DDH in a single center who presented at age <6 months with Ortolani+ hips and were treated with PH. Recommended daily PH wear duration (23 vs. 24 h) and the frequency of clinic visits in first 4 weeks after the initiation of PH treatment were analyzed. The clinical success (stable hip that did not require closed or open reduction or the use of an abduction orthosis) and radiographic success based on the acetabular index at 2-year follow-up were compared between different PH regimen groups. Results: Sixty-two patients (74 hips, 53 females) with Ortolani+ hips had a mean age of presentation of 23±28 days (range, 4 to 128 d) and mean follow-up of 33.2±18.4 months (range, 8 to 85 mo). Overall clinical success rate of PH for Ortolani+ hips was 93% (69/74 hips) and radiographic success rate at 2 years was 84% (48/57 hips). There was no difference in clinical or radiographic success rate between the 23- and 24-hour wear groups ( P >0.99, 0.73) or between hips assessed almost weekly compared with once or twice during the first 4 weeks of PH treatment ( P >0.99 for both). Conclusions: The 23- versus 24-hour PH regimen and frequency of clinic visits in the first 4 weeks of PH treatment did not affect the clinical or radiographic success rate of Ortolani+ hips in infantile DDH. A strict weekly clinic visit and 24-hour PH regimen may not be necessary to obtain stable reduced hips in infants presenting <6 months of age with Ortolani+ hips. Level of Evidence: Level III—therapeutic.